Medical cannabis and cannabis-based medicine show both potential efficacy and potential harms: Cross-sectional comparison with controls on self-rated and interviewer-rated outcomes within the Danish pilot program on medical cannabis. (November 2021) - Kudahl, Benedikte; Berg, Marie Eva; Posselt, Christine Merrild; Nordentoft, Merete; Hjorthøj, Carsten
Abstract: Background and purpose: Denmark launched a pilot program of medical cannabis in January 2018. The aim was to establish whether medical cannabis and cannabis-based medicine (MC/CBM) were superior and safe compared to conventional treatment, regardless of the indications for which people received such medication. Materials and methods: People (cases) were identified who had redeemed at least one prescription of MC/CBM according to the nationwide, unselected Danish registers. These were propensity-score matched to controls with the same indications who had not used MC/CBM. Potential participants were contacted electronically, and if willing to participate filled in various survey instruments online. Participants were also interviewed in person in order to investigate symptoms of depression, anxiety, and to assess cognitive levels. Different sets of analyses were conducted, handling potential confounders in different ways. Results: In the primary analyses, cases were more satisfied with their treatment than were controls (mean (SD) 29.2 (4.8) versus 26.5 (4.5) on the CSQ, p = 0.006), and scored lower on depression (3.3 (3.0) versus 4.6 (2.9), p = 0.03). Cases reported higher levels of pain than controls when measured on the SF-36 bodily-pain subdomain (36.3 (23.0) versus 48.7 (30.1), p = 0.01). There were indications of worse symptoms of multiple sclerosis in cases compared to controls. Reported side-effects were generally mild. Conclusion: Both potential effects and harms of MC/CBM were observed. Randomized trials are required to establish if these are true effects and harms, or due to confounding by indication. Highlights: Patients using medical cannabis or cannabis-based medicine are more satisfied with the treatment than controls using conventional medication for the same disorders. Patients using medical cannabis or cannabis-based medicine may have lower scores of depression than controls using conventional medication, regardless of the disorder for which cannabinoids were used. Patients using medical cannabis or cannabis-based medicine may have higher levels of pain than controls using conventional medication for the same disorders.